A confusion of princes - Nix, Garth (New York : Harper, 2012)
Battling aliens, space pirates, and competitors, Prince Khemri meets a young woman, named Raine, and learns more than he expected about the hidden workings of a vast, intergalactic Empire, and about himself.
Booklist
Horn Book Starred
Publisher's Weekly
Booklist, February 2012
Horn Book Starred, May 2012
Kirkus Starred, March 2012
Keywords: Inheritance and succession -- Juvenile fiction; Princes -- Juvenile fiction; Adventure and adventurers -- Fiction; Inheritance and succession -- Fiction; Princes -- Fiction; Science fiction; Adventure fiction; Inheritance and succession -- Fiction; JUVENILE FICTION / Action & Adventure / General; JUVENILE FICTION / Fantasy & Magic; JUVENILE FICTION / Social Issues / Adolescence; Princes -- Fiction; Science fiction; Adventure fiction; Science fiction